Quantitative evaluation of retinal vascular parameters among highland and lowland native children using artificial intelligence - Bai, Xueqing; Zhang, Chengyue; Wang, Xingye; Tan, Huizhen; Wang, Yinuo; Abula, Alimujiang; Lan, Tianqi; Liao, Yuxiang; Ju, Xiaofang; Quan, Xiaojie; Han, Xue; Zhang, Xue; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTo investigate retinal vascular and optic nerve head (ONH) characteristics in highland- and lowland-dwelling native children using artificial intelligence-based automated quantification of retinal vascular morphology.MethodsThis cross-sectional study analyzed 834 fundus images from 417 children (age 8–9 years), including 123 highland children (HLC) and 294 lowland children (LLC). Fundus photography was performed using a non-mydriatic 45° fundus camera. Automated image analysis quantified: (1) retinal vascular parameters (fractal dimension [VDf], caliber [VC], tortuosity [VT], density [VD], branching angle [VBA], and arteriole-to-venule ratio [AVR]); and (2) optic nerve head morphology (disc area, cup area, and cup-to-disc ratio [C/D]). Group comparisons of all parameters were conducted using AI-based analytical methods.ResultsAfter adjusting for age, sex, and axial length (AXL), covariance analysis demonstrated that the HLC group showed significantly smaller VC (p = 0.005) and VBA (p = 0.003), along with larger optic cup and disc areas (p < 0.001) compared to the LLC group. Both peripapillary VD and VC exhibited a progressive decrease with increasing distance from the optic disc border. Moreover, the HLC group demonstrated a significantly lower VC compared to the LLC group (p = 0.005). Furthermore, the HLC group displayed: (1) significantly higher VD in the inferior quadrant (p < 0.001), (2) increased VT in both nasal and temporal quadrants (p < 0.001 for both), (3) decreased VC in superior (p < 0.001), inferior (p = 0.005), and nasal (p = 0.001) quadrants, and (4) reduced VDf in the nasal quadrant (p = 0.001) of peripapillary regions compared to the LLC group.ConclusionOur findings demonstrate statistically significant differences in retinal vascular and optic nerve head morphology between HLC and LLC. Specifically, the HLC group exhibited significantly reduced VC but larger optic cup and disc areas compared to the LLC group.